Formal and informal natural bathing sites and beaches in the Slovenian coastal zone – challenges in the field of spatial inventory and planning - Čok, Gregor (Annales. Series historia et sociologia, 2024)
The Slovenian coastal zone offers favourable conditions for bathing, which has led to the development of many natural bathing sites and beaches. The article presents the results of the research aimed at recording their legal status, number, extent and capacity. We reviewed official databases, prepared an analysis of the spatial conditions and capacity calculations. The research was based on descriptive and comparative methods and interviews. It was found that there are 17 bathing sites, as recorded in official records, and an additional 29 so-called informal bathing sites located along the entire coastline. The total capacity of all 46 locations is 42,781 bathers. The estimate is almost three times higher than the official data, which addresses the need to upgrade the existing system of spatial recording. Research addresses the analytical approach to assessing conditions in space and contributes to the collection of reliable data.
Keywords: beach carrying capacity assessment; beaches; capacity; coastal zone; evidentiranje; kapacitete; naravna kopališča; natural bathing sites; obalni pas; ocena nosilne zmogljivosti kopališča; plaže; recording